2014
DOI: 10.1002/cctc.201402226
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Hydroformylation of Alkenes by using Carbon Dioxide as the Carbon Monoxide Source in the Presence of Ionic Liquids

Abstract: Dedicated to the memory of Prof. Roberto F. Souza, one of the pioneers of ionic liquid phase organometallic catalysisThe reaction of [BMI·Cl] (BMI = 1-butyl-3-methylimidazolium) or [BMMI·Cl] (BMMI = 3-butyl-1,2-dimethylimidazolium) with Ru 3 (CO) 12 generates Ru-hydride-carbonyl-carbene species in situ that are efficient catalysts for a reverse water gas shift/ hydroformylation/hydrogenation cascade reaction. The addition of H 3 PO 4 increased the catalytic activity of the first step (i.e., the hydrogenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 71 publications
(86 reference statements)
2
45
0
2
Order By: Relevance
“…Cationic counterion of chloride additive and bromide anion subtly impacted on catalytic activity and chemoselectivity (entries 14–21). Although the previous reports indicated the formation of Ru‐carbene complex between Ru 3 (CO) 12 and [Bmim]Cl via the oxidative addition of a C−H imidazolium bond to Ru 0 center, as well the deprotonation of imidazolium to generate N ‐heterocyclic carbine ligand in the presence of base,– the formation of Ru‐carbene complex from [Ru(CO) 3 Cl 3 ] − with [Bmim]Cl was less probable due to high oxidation state of Ru and acidic reaction conditions. The performances of four simple cobalt salts were tested, but none of them was superior to Co 2 (CO) 8 (details see Figure S2 in SI).…”
Section: Resultsmentioning
confidence: 96%
“…Cationic counterion of chloride additive and bromide anion subtly impacted on catalytic activity and chemoselectivity (entries 14–21). Although the previous reports indicated the formation of Ru‐carbene complex between Ru 3 (CO) 12 and [Bmim]Cl via the oxidative addition of a C−H imidazolium bond to Ru 0 center, as well the deprotonation of imidazolium to generate N ‐heterocyclic carbine ligand in the presence of base,– the formation of Ru‐carbene complex from [Ru(CO) 3 Cl 3 ] − with [Bmim]Cl was less probable due to high oxidation state of Ru and acidic reaction conditions. The performances of four simple cobalt salts were tested, but none of them was superior to Co 2 (CO) 8 (details see Figure S2 in SI).…”
Section: Resultsmentioning
confidence: 96%
“…entries 13 and 18, Table ), which blocks the formation of carbenes at the active C2 position. This supports the hypothesis of the formation of these carbene species in the case of ionic liquids that are unsubstituted at the C2 position …”
Section: Resultsmentioning
confidence: 99%
“…This supports the hypothesis of the forma-tion of these carbene species in the case of ionic liquids that are unsubstituted at the C2 position. [31,32]…”
Section: Resultsmentioning
confidence: 99%
“…[32] Generally,s ophisticated ligandsa re required to control the reactivity of [Ru-H] + species andt oi mprove both catalytic activity and selectivity. [24][25][26]29] However, it was reported that the RWGS/hydroformylation path may be favoredi nt he absence of extra ligandsi ft he reaction is performed in the presence of imidazolium salt-based ionic liquids (IL) [30] that can generate in situ abnormal Ru-carbene species( Scheme2) [33] The catalytic speciesg enerated by dissolving Ru 3 (CO) 12 in the ionic liquids1 -n-butyl-3-methyl-imidazolium chloride or 1-nbutyl-2,3-dimethyl-imidazolium chloride are efficient multifunctional catalysts for:( a) reverse water-gas shift, (b) hydroformylation of alkenes, and (c) reductive amination of aldehydes. Thus the reaction of alkenes with primary or secondary amines (alkene/amine, 1:1) under CO 2 /H 2 (1:1) affords the hydroaminomethylations products in high alkene conversions (up to 99 %) and selectivities (up to 96 %).…”
Section: Introductionmentioning
confidence: 99%
“…[28] However, 31 PNMR experiments revealed that this apparent ligand effect wasc aused by the formation of phosphoric acid (H 3 PO 4 )u nder our reaction conditions. [33] It is reasonable to assume, that even in the case of reactions involving CO 2 /H 2 in imidazolium salt IL media, it will be possible to shift the selectivity towards the CO path by fine-tuning the reaction conditions. We report herein that the hydroaminomethylation can be easily performed with the simple catalytic system (i.e.,i midazolium chloride IL/Ru 3 CO 2 / H 3 PO 4 ).…”
Section: Introductionmentioning
confidence: 99%